2010
DOI: 10.1051/agro/2010025
|View full text |Cite
|
Sign up to set email alerts
|

Differences in N uptake and fruit quality between organically and conventionally grown greenhouse tomatoes

Abstract: -Soil-bound intensive greenhouse production has been scrutinized for its sustainability due to contamination of ground water by over-fertilization resulting in leaching of nutrients. As environmental guidelines are becoming more restrictive worldwide, and especially in Europe, many greenhouse growers have converted to more sustainable production systems including rockwool culture with recycled water and organic cropping systems in soil. The increase in popularity of organic production systems has amplified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 35 publications
3
11
1
Order By: Relevance
“…Similar results were found in terms of contents of quercetin and kaempferol in tomato fruit skins, which were exposed to high concentrations of N and harvested in May (Stewart et al, 2001). These results are supported by Gravel et al (2010). These results are supported by Gravel et al (2010).…”
Section: Macro-and Micronutrients and Heavy Metals Induce Changes In supporting
confidence: 82%
“…Similar results were found in terms of contents of quercetin and kaempferol in tomato fruit skins, which were exposed to high concentrations of N and harvested in May (Stewart et al, 2001). These results are supported by Gravel et al (2010). These results are supported by Gravel et al (2010).…”
Section: Macro-and Micronutrients and Heavy Metals Induce Changes In supporting
confidence: 82%
“…These results were opposite to results of several field studies (Clark et al, 1998a(Clark et al, ,b, 1999Drinkwater et al, 1995;Poudel et al, 2001). This difference is probably due to the extremely high levels of organic amendments recommended for organic tomato production in Dutch greenhouses, where tomatoes are harvested from May to December and yields can reach 300-500 metric tons/ha (Gravel et al, 2010). High levels of easily available nitrogen sources, especially nitrate, are generally not associated with soil health , and have sometimes been associated with high susceptibility to Fusarium wilt (Woltz and Engelhard, 1973).…”
Section: Discussioncontrasting
confidence: 57%
“…In autumn 2003, an experiment was set up in two identical greenhouse compartments (150 m 2 each) with a similar history of conventional production to compare various systems of greenhouse tomato production, including an organic soil-bound system and a conventional soil-bound system (Gravel et al, 2010). The soil was a sandy soil with the following characteristics at the beginning of the experiment: pH KCl 5.7; organic matter content 9.3%; clay content (particles < 2 mm) 8%; CaCO 3 0.2%.…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
“…For instance, Cardoso et al (2011) concluded that there was no evidence of nutritional superiority of organically grown fruits (acerola, strawberries and persimmon) regarding vitamin C and carotenoids contents. Also, Gravel et al (2010) found little differences in what concerns to taste and nutritional value of organic and conventionally grown tomatoes in greenhouses.…”
Section: Introductionmentioning
confidence: 91%